Teaching and Learning Management in Educational Administration Programs for Developing Administrators in the BANI World Era: A Mixed-Methods Study - Lapho, Thitikamolsiri; Punyaburana, Orn-usa (วารสารศึกษาศาสตร์ มหาวิทยาลัยสงขลานครินทร์ วิทยาเขตปัตตานี, 2026)
This study aimed to examine teaching and learning management in educational administration programs for developing educational administrators in the BANI World era. A convergent mixed-methods design was employed. Quantitative data were collected from 124 participants selected through convenience sampling, comprising graduate employers (n = 56), instructors (n = 5), and graduate students (n = 63). Qualitative data were obtained through semi-structured interviews with five purposively selected graduate employers. The research instruments consisted of a five-point rating scale questionnaire and a semi-structured interview protocol. Quantitative data were analyzed using frequency, percentage, mean, and standard deviation, while qualitative data were analyzed using content analysis. The findings showed that the overall perceptions of all respondent groups toward teaching and learning management were at the highest level (X̄ = 4.74). All individual items were also rated at the highest level. The highest-rated item was effective management of the teaching process (X̄ = 4.84), followed by consistent monitoring of learning progress (X̄ = 4.83), student–instructor relationships (X̄ = 4.82), opportunities for student expression (X̄ = 4.81), and diverse and authentic assessment (X̄ = 4.81). Qualitative findings identified five key components of teaching and learning management for developing educational administrators in the BANI World era: (1) instructional management and the role of educators, (2) student development promotion, (3) learners’ skills and experiences, (4) technology and instructional resources, and (5) assessment and evaluation. These findings suggest that educational administration programs should emphasize these components to better prepare educational administrators for the BANI World era.